Anarchist Participatory Development: A Possible New Framework?. Issue 4 (17th December 2014) - Wald, Navé; Arsel, Murat
ABSTRACT This article examines the ongoing critiques and debates around the 'participatory turn' in development theory and practice and suggests anarchism as a practice‐oriented theoretical framework for engaging with what participatory development ought to achieve. Explicit links are constructed between key terms in these development debates and anarchist political philosophy, and a call is made for greater attention to anarchism as a theoretical framework for radical and transformative development practice. This article then analyses empirical experiences of 'anarchistic partnerships' between development experts and grassroots peasant‐indigenous organizations in north‐west Argentina, who, although not self‐identifying as anarchist, adhere to ideals such as horizontal prefigurative politics and radical democracy that are effectively anarchist in their orientation. These experiences challenge the NGO–social movement divide and offer a virtually unexplored form of radical development practice that is worthy of further academic attention. Thus, while this article is concerned with familiar debates in development studies, it offers some preliminary directions for advancing theoretical and practical knowledge regarding transformative participation.